Study of discrepancy in subjective and objective cognitive function in patients with depressive disorder - Fu Linna; Wang Min; Yang Xiao; Dou Yikai; Wei Jinxue; He Zongling; Yu Yue; Cai Xiao; Ma Xiaohong (Sichuan jingshen weisheng, 2024)
BackgroundThere exist differences in the subjective and objective cognitive functions of patients with depressive disorder， ane there are limited research on influencing factors of such phenomenon currently.ObjectiveTo explore the differences in subjective and objective cognitive function in patients with depressive disorder as well as influencing factors， and to provide references for further understanding of cognitive impairment in patients with depressive disorder.MethodsA total of 77 patients with depressive disorder who received outpatient or inpatient treatment in the Fourth People's Hospital of Chengdu from January 13， 2022 to December 11， 2023 were selected for the study. These patients also met the diagnostic criteria of Diagnostic and Statistical Manual of Mental Disorders， fifth edition（DSM-5）. Various tools were employed to assess patients in this study： Montgomery-Asberg Depression Rating Scale （MADRS） for the depressive symptoms， Perceived Deficits Questionnaire for Depression （PDQ-D） and Chinese Version of Brief Neurocognitive Test Battery （C-BCT） for the subjective and objective cognitive function， Sheehan Disability Scale （SDS） for the social function， and Clinical Global Impression-Severity of Illness（CGI-SI） for the severity of patient's condition. Pearson correlation analysis was used to examine the correlation of subjective and objective cognitive function and their differences with age， years of education， MADRS total score， SDS total score， and CGI-SI score. Multiple linear regression was used to explore the influencing factors of the differences between subjective and objective cognitive function.ResultsThere was a statistically significant difference in the total PDQ-D scores and the difference of subjective and objective cognitive function （D value） between depressive patients with and without medication （t=-4.228， -2.392， P<0.05 or 0.01）. There was no statistically significant correlation in subjective and objective cognitive function in patients with depressive disorder （r=-0.148， P>0.05）. Negative correlations can be observed between the PDQ-D total score and age or years of education （r=-0.333， -0.369， P<0.01）. The PDQ-D total score was positively correlated with MADRS total score， SDS total score and CGI-SI score （r=0.487， 0.637， 0.434， P<0.01）. D value was negatively correlated with age and years of education （r=-0.411， -0.362， P<0.01）， while positively correlated with MADRS total score， SDS total score and CGI-SI score （r=0.259， 0.468， 0.299， P<0.05 or 0.01）. Age （β=-0.328， P<0.01） and SDS total score （β=0.409， P<0.01） were two predictive factors for D value.ConclusionThe difference between subjective and objective cognitive function among patients with depressive disorder is related to several factors including age， years of education， severity of symptoms and impairment of social function. ［Funded by Surface Project of National Natural Science Foundation of China （number， 62173069）； Technological Innovation 2030-Major Project of "Brain Science and Brain-Like Research" （number， 2022ZD0211700）； Key R&D Support Program and Major Application Demonstration Project of Chengdu Science and Technology Bureau （number， 2022-YF09-00023-SN）］